Inhaled nitric oxide in premature infants for preventing bronchopulmonary dysplasia: a meta-analysis - Yi Zheng; Qi Wu; Shuping Han (BMC Pediatrics, 2023)
Abstract Background The effectiveness of nitric oxide (NO) in reducing the risk of bronchopulmonary dysplasia (BPD) remains debatable. In this study, we performed a meta-analysis to guide clinical decision-making regarding the significance of inhaled NO (iNO) on the potential occurrence and outcomes of BPD in premature infants. Methods Data from clinical randomized controlled trials (RCTs) published in PubMed, Embase, Cochrane Library, Wanfang, China National Knowledge Infrastructure (CNKI) and Chinese Scientific Journal Database VIP databases for premature infants were searched from inception to March 2022. Review Manager 5.3 statistical software was used for heterogeneity analysis. Results Of the 905 studies retrieved, 11 RCTs met the screening criteria of this study. Our analysis showed that the iNO group was associated with a significantly lower incidence of BPD than the control group (relative risk [RR] = 0.91, 95% confidence interval (CI) 0.85-0.97, P = 0.006). We also observed no significant difference in the incidence of BPD between the two groups at the initial dose of 5 ppm (ppm) (P = 0.09) but those treated with 10 ppm iNO had a significantly lower incidence of BPD (RR = 0.90, 95%CI 0.81-0.99, P = 0.03). However, it should be noted that although the iNO group had an increased risk for necrotizing enterocolitis (NEC) (RR = 1.33, 95%CI 1.04-1.71, P = 0.03), cases treated with an initial dose of 10 ppm revealed no significant difference in the incidence of NEC compared with the control group (P = 0.41), while those treated with an initial dosage of 5 ppm of iNO had a significantly greater NEC rates than the control group (RR = 1.41, 95%CI 1.03-1.91, P = 0.03). Further, we observed no statistically significant differences in the incidence of in-hospital mortality, intraventricular hemorrhage (IVH) (Grade 3/4) or periventricular leukomalacia (PVL) and pulmonary hemorrhage (PH) between the two treatment groups. Conclusions This meta-analysis of RCTs showed that iNO at an initial dosage of 10 ppm seemed more effective in reducing the risk of BPD than conventional treatment and iNO at an initial dosage of 5 ppm in preterm infants at a gestational age of ≤34 weeks who required respiratory support. However, the incidence of in-hospital mortality and adverse events between the overall iNO group and Control were similar.